The Human Factor In Knowledge Management A Case Study At Multimedia University - Pei, Ng Sin (2004)
This study mainly examines the factors affecting the willingness of organizational members to share knowledge via MMU ShareNet. Besides that, it compares the factors affecting the willingness to share knowledge via MMU ShareNet on various categories of the five demographic factors that basically include position, gender, working experience in the University, academic level and age. Additionally, it also investigates the effectiveness of rewards towards knowledge sharing via MMU ShareNet.